The Oxford handbook of Greek and Roman art and architecture - Marconi, Clemente (Oxford Univ. Press, 2014)
This handbook explores key aspects of art and architecture in ancient Greece and Rome. Drawing on the perspectives of scholars of various generations, nationalities, and backgrounds, it discusses Greek and Roman ideas about art and architecture, as expressed in both texts and images, along with the production of art and architecture in the Greek and Roman world.
Literaturangaben
Keywords: Aufsatzsammlung; Geschichte; Architektur; Kunst; Römisches Reich; Griechenland